Analisis Pengaruh Pelatihan Terhadap Kinerja Karyawan Di Kantor PT. Pembangkitan Jawa-Bali Unit Pembangkitan Brantas - Permana, Yoda; Novadjaja, Lily Hendrasti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research basically aimed to determine the effect of trainingfor employee performance. The site chosen for this study is the PT. Pembangkitan Jawa Bali Unit Pembangkitan Brantas. This research was conducted to 56 respondents using a quantitative approach. Thus, the data analysis is the statistical analysis in the form of multiple linear regression. The results showed that these three independent variables (coach quality, training method, and training experience) simultaneously significant effect on employee performance by test F = 16.844 (Sig. 001). While the effect of partial, coach qualityvariables significantly influence employee performance with sig. 0,011 (t = 5,623). Second variable has sig. 0,047 (t=2,395), and third variable has sig. 0,022 (t=3,248). The first independent variable was also found that coach quality is the most variable has an impact on employee performance. Â Keywords:training, coach quality, training method, training experience, employee performance, PT. Pembangkitan Jawa Bali Unit Pembangkitan Brantas